Locating production and income within MNEs: An alternative approach based on formulary apportionment - Dylan G. Rassier (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2014)
Given the unique products and the complex global structure of some MNEs, the economic substance of transactions within MNEs is often subject to question under separate accounting. For statistical purposes, formulary apportionment is a viable alternative to separate accounting as a method for locating production and income within MNEs.
Keywords: 330